Measuring the Difficulty Level of Mathematical Problems Based on Polya Criteria - Nurhalimah, Atin; Mandailina, Vera; Mahsup; Syaharuddin (Journal of Education Reseach and Evaluation, 2022)
Mathematics learning needs to be directed in understanding mathematical concepts and principles because it will be necessary for solving mathematical problems, problems in other disciplines, and problems in everyday life. But sometimes, we make mistakes both intentional and unintentional so that they will have an impact on the results of the mathematical problems we work on. Today many studies discuss the difficulty of students in solving math problems but there has been no research that discusses further the level of difficulty. This study aims to analyze the level of error students solve math problems according to Polya criteria, student errors based on education level, based on focus areas, and student errors based on other moderator variables. The method in this study uses meta-analysis. Data must meet the inclusion and exclusion criteria of indexing databases such as Scopus, DOAJ, WorldCat, Google Scholar, and Garuda Portal. The data was analyzed using JASP software. The results showed that of the 53 data that met the eligibility criteria obtained error rate information on criteria (1) understanding of problems by 37%, (2) devising a plan by 36%, (3) carrying out the plan by 36%, and (4) looking back by 44%. Based on the focus field focus obtained the RE Model for the highest error is in the case of number patterns when compared to algebraic and geometric cases.